Note on Dr. Lange's Interest Theory - Knight, Frank H. (Review of Economic Studies, 1937)
Journal Article Note on Dr. Lange's Interest Theory Get access Frank H. Knight Frank H. Knight Chicago Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 4, Issue 3, June 1937, Pages 223–230, https://doi.org/10.2307/2967457 Published: 01 June 1937